Tabata training to improve VO2 max endurance in monda fc male futsal players - Suprawesta, Lalu; Zainuddin, Fadli; Yusuf, Putra Muhammad (Universitas Tanjungpura, 2025)
Background. VO2 max endurance capability is one of the crucial physical conditions in playing futsal. VO2 max endurance can be improved through cardiorespiratory exercises. High-intensity interval training, such as Tabata, is a cardio exercise that can contribute to enhancing VO2 max endurance. Objectives. The aim of this study to investigate the influence of Tabata training in an effort to enhance VO2 max endurance in male futsal players of Monda FC. Methods. This experimental study employed a one-group pretest-posttest design on all male futsal players of Monda FC who underwent VO2 max endurance examinations before and after the training. The sampling technique used is total sampling, where a population contain a total of 15 players included in the study. Tabata training was administered three times a week over a 4-week period, with five sessions per day lasting 20 minutes each and consisting of 40 sets. Each set of movements occurred for 20 seconds with a 10-second interval. A paired sample t-test was utilized for data analysis. Results. The results of the Tabata training showed an increase in the average VO2 max endurance of Monda FC male futsal players from a sufficient level (36.4 ±6.1 ml/kg/minute) to a good level (43.5 ±5.9 ml/kg/minute) after conducting training three times a week for four weeks. Conclusion. High-intensity interval training such as Tabata can enhance VO2 max endurance in futsal players, which is crucial for improving technical and tactical skills while avoiding injuries during matches. These findings highlight the practical benefit of integrating structured training of Tabata as the HIIT protocols into youth futsal training programs.